Monitoring, reporting, and verification requirements and implementation costs for climate change mitigation activities: Focus on Bangladesh, India, Mexico, and Vietnam - Basak R (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2016)
This report describes and estimates implementation costs for key monitoring, reporting, and verification (MRV) requirements for low emissions development programs requiring MRV systems. MRV system development and setup costs vary significantly—from a low of $210,000 to a high of $2.44 million—mostly due to the area covered by the Nationally Appropriate Mitigation Action program and the number of participating farmers. Therefore the cost of printing and distributing cultivation logbooks is greater (a key component of data collection). Cultivation logbooks account for over two-thirds of all first-year costs and can reach $2.2 million in the case of India, where reaching one-third of farmers means over 18.5 million logbooks would be required. Finding an alternative to a printed paper booklet to record key cultivation data in a standardized fashion throughout the project’s life cycle could help to drive down this cost. Ongoing MRV implementation costs may reasonably amount to less than $55,000/year across the four countries and systems studied. Annual monitoring costs could be kept low by collecting data on field size and sustainable development indicators (e.g., tonnes of cereal produced, water usage, revenues) from a random sample of 384 participating farmers. Also, efforts to use existing data-gathering and management systems as much as possible through strategic partnerships with domestic institutions and implementing partners would help to drive down costs while also increasing the quality of MRV systems.